2022
DOI: 10.1007/s42979-022-01340-5
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to an Open-Source Map-Matching Approach for Big GPS Data

Abstract: This work shows how map-matching helps to minimize errors in GPS data by finding the most probable corresponding points of the recorded waypoints of a trajectory on a road network. We investigate an open-source alternative for map-matching trajectories called Valhalla, which could replace limited and costly commercial map-matching services. Valhalla is an open-source routing engine, which provides different services, such as path-finding, map-matching, and generating maneuvers based on a path. We build a cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…If, on the other hand, no such route exists (i.e., mapMatchedTrajectory is nil at Line 7, Algorithm 2), the trajectory is discarded as unfeasible. An approach to map matching similar to the one adopted in the present study was recently presented by Saki and Hagen in [48]. In that study, the authors reported that the solution was able to correctly map match approximately 95% of the input trajectories.…”
Section: Empirical Procedurementioning
confidence: 80%
“…If, on the other hand, no such route exists (i.e., mapMatchedTrajectory is nil at Line 7, Algorithm 2), the trajectory is discarded as unfeasible. An approach to map matching similar to the one adopted in the present study was recently presented by Saki and Hagen in [48]. In that study, the authors reported that the solution was able to correctly map match approximately 95% of the input trajectories.…”
Section: Empirical Procedurementioning
confidence: 80%
“…They defined the map-matching problem as finding the sequence of street segments most likely to match the sequence of GPS points. We used the routing engine Valhalla in our research project ( 31 ). Alternatively, we could have completely removed the points with poor accuracy from the data.…”
Section: Methodsmentioning
confidence: 99%
“…SageMaker is a machine-learning platform that makes it easy for scientists and developers to build, train, and deploy machine-learning models [49]. These models can predict learning outcomes based on historical data and provide insights to personalize the educational experience in the metaverse.…”
Section: ) Big Data Analyticsmentioning
confidence: 99%